Sensory characteristics and consumer segmentation of fried sweetpotato for expanded markets in Africa - Dery, E.; Carey, E.E.; Ssali, R.T.; Low, Jan W.; Johanningsmeier, S.D.; Oduro, I.; Boakye, A.; Omodamiro, R.M.; Yusuf, H.L. (Wiley, 2020)
Prepared foods are increasing in popularity in West Africa alongside rapid urbanisation. Growing demand for fried products calls for targeted breeding efforts to meet consumer needs, but little is known regarding consumer preferences. This research identified the sensory attributes of fried sweetpotato preferred by different consumer groups using a combination of consumer acceptance testing and descriptive sensory analysis. Market and community surveys identified three consumer segments in Ghana and Nigeria with contrasting preferences for fried sweetpotato sensory attributes. One group preferred crispy, crunchy, mealy and sweet fried sweetpotato; another preferred characteristic yam flavour and dry texture; and the third preferred uniform orange colour appearance, ripe plantain flavour and palm nutty flavour. Such consumer segmentation can help emerging West African fried sweetpotato industries identify target markets and provides valuable information to breeders, growers and retailers to prioritise attributes in their breeding, growing or product sourcing decisions.